Relationship between Individual Attributional Style, Self-Esteem, Locus of Control and Academic Achievement of Vytautas Magnus University Students - Laima Ruibytė (Lithuanian Sports University, 2018)
This study was aimed to investigate the link between students' self-esteem, individual attribution style, locus of control and academic achievement for better understanding of students' learning and adaptation problems. The main purpose of the research was to examine the relationship between the individual attributional style, locus of control and self-esteem, analyse, to analyze how these features of personality were related to future aspirations and how the afore-mentioned features were reflected in the academic activity of students. The tasks set for the analysis of the survey data were as follows: to identify specific features of self-esteem, locus of control and attributional style and their interrelation, analyse the link between self-esteem and future aspirations of the individual, and identify the link of self-esteem and locus of control with academic grade. Participants were 200 Vytautas Magnus University students (59 males and 141 females). For the purpose of survey we used the questionnaire of 52 items constructed by us which comprised three blocks: self-esteem, attributional style and locus of control. Self-esteem of students was measured using Rosenberg (RVS) self-esteem scale (10 statements). To determine specific features of attribution (15 questions) we used the respondents' opinion regarding their colloquium grade (two questions) and interpretation of reasons for getting such grade (eight questions) based on B. Weiner's model (Weiner, 1985). One question reflected the student's expectations before the exam and one was intended to determine the student's attribution style in foreseeing the factors predefining the future result. The scale of the locus of control (27 statements) was worked out on the basis of the Subjective Control Level (УСК) survey methods developed by the Scientific Research Institute of Bechterev and the Occupational Stress Indicator (OSI) Methods created according to the Dutch version of Spanningseter. The main conclusions are: 1. The survey results confirmed the interrelationship between self-esteem and internality (externality) - students with higher level of self-esteem have higher internality score. 2. Low and high self-esteem students explain their success using different attributional style. Boys and girls with higher level of self-esteem attached greater importance to their internal and stable features and valued unstable external factors less than low self-esteem students. 3. In addition to different interpretation of current events, students-internals and externals also had different perception of their future result. Externals more than internals were inclined to believe that their examination grade would be predetermined by external causes. 4. Subjective locus of control was linked to results and achievements of individual activities. Girl-students with relatively higher internality had better results in academic activities, i.e. their received grade than girl-students externals. The data on boys did not reflect statistically reliable link between internality and received grade. 5. Level of internality keeps growing with age. Particularly distinct is the dependence of internality upon the year of studies in which the respondents are studying. Senior girls and boys manifest higher level of internality. It seems that students' attributions, locus of control, self-esteem and academic achievement are strongly connected and thus they have to be applied for effective teaching. Keywords: individual attribution style, self-esteem, locus of control, academic achievement.